A Life Worth Living: Value and Responsibility. Issue 2 (16th March 2019) - Goodnight, Audra L
Abstract: Value and responsibility are two central concepts in philosophy and bioethics. The articles that comprise this issue of The Journal of Medicine and Philosophy engage topics of moral injury, madness, transhumanism, cognitive enhancement, and the woman's responsibility to assist her fetus. Clearly diverse in matter, these subject articles univocally present fruitful ground for engagement with contemporary questions that impact society today. The ability to cure or to enhance, to treat or to terminate through advances in medical technology are all actions that come with personal and social responsibility for their consequences. By approaching each article through the dual lens of value and responsibility, the reader is challenged to think seriously about the values we hold as human persons and the responsibility we take to pursue and protect these values .